Oral versus subcutaneous semaglutide for prevention of major adverse cardiovascular events: cost per outcome analysis of SUSTAIN-6 and PIONEER-6. Issue 7 (3rd October 2022) - Hammerman, Ariel; Moore, Candace Makeda; Aboalhasan, Enis; Azuri, Joseph; Arbel, Ronen
ABSTRACT: Background: Semaglutide, a glucagon-like peptide-1 receptor agonist (GLP1a), reduces the risk of major adverse cardiovascular events (MACE) in patients with Type 2 diabetes mellitus (T2DM). An oral version of semaglutide is now available, and patients may prefer it over the subcutaneous form. Our objective was to compare the value for money of the two modalities by assessing the cost needed to treat (CNT) to prevent MACE. Methods: The CNT to prevent MACE was figured by multiplying the one-year number needed to treat (NNT) with either oral or subcutaneous semaglutide by the annual cost of therapy. Efficacy estimates and the resulting NNT figures were extracted from the published results of the SUSTAIN-6 and the PIONEER-6 trials for the injectable and oral versions of semaglutide, respectively. Drug costs were estimated as 75% of the United States national average drug acquisition cost listing in June 2021. We performed a scenario analysis to mitigate the primary differences between the populations in the two trials. Sensitivity analysis was performed to evaluate the effect of price changes of the interventions. Results: The CNT to prevent one MACE with subcutaneous semaglutide in SUSTAIN-6 was $966, 693 ($594, 888-$5, 035, 302) compared to $948, 689 ($463, 465-∞) with oral semaglutide in PIONEER-6. The scenario analysis demonstrated a 17% lower CNT for oral semaglutide. The difference between CNTs was sensitive to price fluctuations of the two interventions. Conclusions: Oral and subcutaneous semaglutide prescribed to prevent MACE in patients with T2DM provide similar value for money. The choice between both therapies should be guided mainly by patient preferences.